The role of women as a key axis in history - Pro Velasco, María Luisa (2021)
The role played by women in our society has changed over time. This article studies the history of women's liberation movement. It covers from the sexual revolution, in two different moments, to feminism, which has been the major player in the struggle to improve the situation, and it currently presents various expressions.